Antibacterial and Anti-Inflammatory Potential of Polyherbal Formulation Used in Chronic Wound Healing. (7th July 2021) - Mandrika, Ilona; Kumar, Somit; Zandersone, Baiba; Eranezhath, Sujith Subash; Petrovska, Ramona; Liduma, Iveta; Jezupovs, Arnolds; Pirags, Valdis; Tracevska, Tatjana
Abstract : Objective . Polyherbal formulations Jathyadi Thailam and Jatyadi Ghritam ( JT ) are used in Indian traditional medicine for diabetic chronic wounds, fistula, fissure, eczema, and burn management. We aimed to investigate the antibacterial and anti-inflammatory properties of crude hexane and ethanol extracts of JT formulations. Methods . Antibacterial activity of JT extracts was tested to estimate minimum inhibitory concentrations (MICs) against nine reference bacterial strains, including one methicillin-resistant Staphylococcus aureus (MRSA) and multidrug-resistant (MDR) Pseudomonas aeruginosa, and clinical strains of methicillin-susceptible S.aureus (MSSA), all involved in diabetic foot infection. The anti-inflammatory activity of plant extracts was evaluated in LPS-treated macrophage cells by measuring the mRNA levels and secretion of inflammatory mediators. Results . The antibacterial activity of JT extracts was higher against Gram (+) bacteria, with the MICs varying from 1.95 to 62.5 mg/mL. Gram (−) bacteria were only susceptible to ethanol extracts of JT . Plant extracts were found to be the most active against the reference and clinical strains of MSSA, MRSA, and biofilm-forming S. epidermidis . JT extracts efficiently inhibited in a dose-dependent manner the mRNA expression and protein secretion of proinflammatory cytokines IL-6 and IL-1 β, and chemokines MCP-1 and CXCL10 in LPS-challenged macrophages. Conclusion . In the present study, we have shown that extracts of JT formulations possess potent antibacterial and anti-inflammatory properties that could be involved in chronic wound healing activity and has the potential to be used as external add-on therapy in the management of multidrug-resistant bacterial infections at the wound.